Validation of the clinical assessment scale for autoimmune encephalitis in a severe autoimmune encephalitis cohort - He, Yu; Li, Fangfang; Yang, Ali; Yu, Chen; Wang, Yifan; Zhao, Jing; Zang, Weizhou (Frontiers in Immunology, 2024)
ObjectiveThe Clinical Assessment Scale for Autoimmune Encephalitis (CASE) is a novel tool tailored specifically for evaluating the severity of autoimmune encephalitis (AE). However, its application in severe AE patients is limited. This study aimed to evaluate the reliability and validity of the CASE and explore its clinical significance in a severe AE cohort.MethodsThe relevant clinical characteristics, laboratory data, and prognosis of patients diagnosed with severe AE between April 2017 and April 2023 were collected. The CASE and modified Rankin scale (mRS) were performed at admission, discharge, and 1-year follow-up, respectively. The reliability of CASE was validated by calculating the Cronbach’s alpha value. The validity was evaluated by calculating the Spearman’s rank correlation with the corresponding mRS. Univariate and multivariate logistic regression were utilized to identify risk factors for poor prognosis.ResultsA total of 140 patients were recruited for the study. The CASE scale presented great internal consistency, with Cronbach’s α value of 0.768 for the total score. The Spearman’s rank correlation analysis revealed strong criterion validity between CASE and mRS, with coefficients of 0.68, 0.92, and 0.95 at admission, discharge, and 1-year follow-up, respectively (all p < 0.001). ROC analysis identified CASE score at admission served as a promising predictive marker for clinical response to treatment, with an AUC of 0.67 (95% CI: 0.57-0.77, p = 0.003). The optimal cut-off point was 22.5. At 1-year follow-up, 72/140 (51.4%) patients achieved good functional status (mRS, 0-2). Multivariate logistic regression confirmed that higher CASE scores on admission and older age at onset were associated with poor short-term as well as 1-year prognosis, respectively. In addition, no clinical response to treatment (OR = 40.499; 95% CI: 7.077-231.746, p < 0.001) and longer duration of hospitalization (OR = 1.071; 95% CI: 1.017-1.128, p = 0.010) were associated with poor function states at 1-year follow-up.ConclusionThe CASE has proven suitable for evaluating disease severity and prognosis in severe AE patients. Besides, CASE score, age at disease onset, hospital stays, and response to immunotherapy are identified as independent risk factors for unsatisfactory prognosis in severe AE patients.